Catalytic Asymmetric Strecker Reaction: Bifunctional Chiral Tertiary Amine/Hydrogen-Bond Donor Catalysis Joins the Field - Liu, Yun-Lin; Zhou, Jian (Synthesis, 2015)
Bifunctional chiral tertiary amine/hydrogen-bond donor catalysis has recently emerged as a powerful strategy for developing catalytic asymmetric Strecker reactions for the synthesis of various types of optically active α-amino nitriles, useful as versatile building blocks for the synthesis of value-added products such as α-amino acids, 1,2-diamines, or heterocycles. This short review discusses the advantages of this strategy, summarizes recent advances, and describes the synthetic opportunities that remain open.1 Introduction2 Tertiary Amine/Hydrogen-Bond Donor Catalysis of Asymmetric Strecker Reactions3 Summary and Outlook
Keywords: Strecker reactions; asymmetric catalysis; nitriles; imines